Menguji Komitmen Organisasional sebagai Variabel Mediasi antara Ketidakamanan Kerja dan Turnover Intention - Sri Ekanti Sabardini; Djoko Wijono; Mekar Dewi Fatimah (Universitas Proklamasi 45, 2022)
This study aims to determine the effect of Job Insecurity on Turnover Intention either directly or through the variable Organizational Commitment. The study was conducted on all employees (85 people), a beauty care product company, CV Magic Skin Yogyakarta. Data analysis was carried out using Smart PLS-SEM. The research resulted in an answer that there was a direct influence between Job Insecurity on Turnover Intention, and no influence between Job Insecurity and Organizational Commitment, and no influence between Organizational Commitment and Turnover Intention. Job insecurity also has no effect through the variable Organizational Commitment to Turnover Intention. In addition, the results also show that there are indicators of work insecurity that can no longer be used to measure work insecurity.